Artists' Pages: A Site for the Repetition and Extension of Conceptual Art. (1st October 2016) - Ismail-Epps, Samantha
Abstract : In the late 1960s, artists utilized documents such as floor plans, maps, instructions, correspondence, and photographs to record ideas or to take the place of artworks that need not be built. These documents were reproduced through the pages of inexpensive publications, intended to be accessible to wider, globalized audiences beyond the scope of physical exhibitions. This article argues that the page offers transformative qualities and functions as a medium for taking original, unique, and personal documents into the public domain; the page is repeatable, mass-produced, and puts art in the hands of the reader. Through using the pages that artists contributed to exhibition catalogs including Prospect 69, Konzeption/Conception, and July August September (all 1969), this article investigates the various ways in which artists adopted the medium of the page to extend the reach of their ideas and facilitate insights into their thinking and making processes. Working from the premise that artists were in the best position to explain their own work, the investigation conducts close readings of selected pages to discover the different functions of catalog contributions alongside, instead of, and after artworks were exhibited.